Phytochemical analysis and antioxidant potential of Pseudolachnostylis maprouneifolia - Singh, Indra Sen; Kwalyambumu, Derrick Sitali (Journal of Phytology, 2024)
Pseudolachnostylis maproneifolia is a popular medicinal plant, particularly revered in the eastern province of Zambia, especially within Petauke District. Despite its widespread application in traditional medicine, the chemical composition of this plant has not been studied so far. Consequently, there was a pressing need to investigate the medicinal potential of its leaf extract. This study was carried out through preliminary phytochemical screening and GC-MS analysis of the ethanolic extract. The phytochemical profile revealed various secondary metabolites endowed with antifungal, anti-inflammatory, anti-tumor, anti-cancer, antibacterial, antiviral, and antioxidative properties. To quantify its medicinal potential, the total flavonoid content (TFC) and total phenolic content (TPC) was determined using a UV-Vis spectrophotometer. The methanolic extract exhibited a TFC of 157.20 mg QE/g and a TPC of 63.75 mg GAE/g, with an IC50 value of 45.57 μg/mL, signifying a strong antioxidant capability. Notably, the IC50 value of the standard (ascorbic acid) was 23.19 μg/mL. Further analysis involved quantifying the mineral elements crucial for treating anemia, such as iron, copper, zinc, and manganese. AAS based analysis revealed concentrations of these elements to be relatively higher, indicating their suitability for treating anemia. Complementing these findings, in silico molecular analysis and ADMET analysis of five selected phytochemicals, along with a reference cancer drug, yielded promising results such as a highest binding energy of -9.01 Kcal/mol, high gastrointestinal absorption and the lowest inhibition constant of 249.88 nM. These outcomes strongly advocate for subsequent in vitro and in vivo studies on these molecules, supporting their importance as potential drug candidates for cancer drug development.